Formulasi Pendidikan Islam dan Pendidikan Etika Ibnu Maskawaih - Wahid, Lalu Abdurrahman (Lembaga Yasin AlSys, 2021)
This study aims to determine the concept of ethical education thinking formulated by Ibn Maskawaih. This research uses aapproachlibrary research. The result of this research is that Ibn Maskawaih's educational thinking is actually more inclined to morals and ethics. Human ethics in the perspective of Ibn Maskawaih can be classified into two, namely the first, the natural and the second, the other character is obtained through habit and practice. The perspective developed by Ibn Maskawaih that the character or ethics derived from human character can be changed depending on the extent of business, education and environment. Ethical education from Ibn Maskawaih's perspective is based on the concept of human beings, where the task of ethical education is to strengthen the positive forces possessed by human beings in order to achieve a balanced human level so that deeds that are simply good and born spontaneously. With the application of ethics, then in his life, man is expected to be a perfect human being which he calls isabah al-khuluqi al-syarif (the formation of a noble ethical personality). This concept is in line with the current era as a stimulus for education to continue to formulate ethical education that is able to survive in the midst of current moral degradation.